A Study on the Growth and Biochemical Responses in Selected Crops to Electromagnetic Field - Ooi, Bee Bee (2003)
Electromagnetic field (EMF), a non-ionizing radiation exists in abundant in the vicinity of high voltage power lines, which covers a large area of the agricultural land. The study on the effects of EMF on biological system has been rare in the country; therefore, the study on the growth and biochemical responses of plants to EMF would provide new and important knowledge to the agricultural industry. The study was divided into three parts, namely the effects of high electric field on Oncidium taka PLBs, the effects of high electric field as a seed treatment on soybean, radish and papaya, and the effects of EMF from electric power lines on leaf mustard and oil palm. The high electric field strength used in the study was 0, 10, 20, 40, 60, 80, 100 and 120 kV/m. The biochemical changes in leaf mustard planted at 0, 3, 6, 9, 10, 12, 15, 18, 20, 21, 30, 40, 50 and 60 m away from the 33 kV power line and at 0, 10, 20, 30, 40, 50, 60 and 70 m away from the 275 kV power lines were studied. The effects o f EMF from 275 kV power lines were also studied on seven years old oil palm trees which were exposed to EMF for that period and six months old oil palm trees which were exposed to EMF for that period of time a distance of 0, 8.8, 17.6, 26.4, 35.2, 44, 52.8 and 61.6 m away from the lines.